2010
DOI: 10.1007/s10916-010-9619-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Point-of-Care HIV/Aids Medication Dosing Support System Using the Android Mobile Platform

Abstract: Medication dosing errors can greatly reduce HIV treatment effectiveness as incorrect dosing leads to drug resistance and non-adherence. In order to dose correctly, HIV therapy providers must balance several patient characteristics such as renal functions and weight. In developing countries and other resource-limited settings, dosing errors are more likely because treatment is provided by mid-level providers with only basic training in HIV therapy. These providers also typically lack electronic tools informing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Engineers have created various microscopes that attach to smartphones, providing a cost-effective and mobile way to bring more technology to poor and rural regions [50-52]. Development of point-of-care apps for human immunodeficiency virus (HIV) infection treatment to support physicians with limited HIV training in undeveloped regions is expected to minimize errors and improve outcomes [53]. …”
Section: Resultsmentioning
confidence: 99%
“…Engineers have created various microscopes that attach to smartphones, providing a cost-effective and mobile way to bring more technology to poor and rural regions [50-52]. Development of point-of-care apps for human immunodeficiency virus (HIV) infection treatment to support physicians with limited HIV training in undeveloped regions is expected to minimize errors and improve outcomes [53]. …”
Section: Resultsmentioning
confidence: 99%
“…Simple prototype applications for ordering of essential medical supplies and reports about stocktaking have been developed and could be tested in pilot studies [30,38]. Similarly, a recent study has shown the potential of an android application in helping health workers optimise drug dosage schemes for antiretroviral therapy [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Examples of m-health apps are: mobile personal health records (mPHRs) [9,10], apps for diabetes [11], apps for older adults [12] and apps for emergency healthcare support [13][14][15][16]. In difficult areas, m-health apps can help combat endemic and epidemic diseases [17,18] since countries in which such diseases are widespread have to overcome the challenges related to blood safety and availability [19,20].…”
Section: Introductionmentioning
confidence: 99%